Artificial Learning and Machine Learning Applications in Spine Surgery: A Systematic Review. Issue 7 (September 2022) - Lopez, Cesar D.; Boddapati, Venkat; Lombardi, Joseph M.; Lee, Nathan J.; Mathew, Justin; Danford, Nicholas C.; Iyer, Rajiv R.; Dyrszka, Marc D.; Sardar, Zeeshan M.; Lenke, Lawrence G.; Lehman, Ronald A.
Objectives: This current systematic review sought to identify and evaluate all current research-based spine surgery applications of AI/ML in optimizing preoperative patient selection, as well as predicting and managing postoperative outcomes and complications. Methods: A comprehensive search of publications was conducted through the EMBASE, Medline, and PubMed databases using relevant keywords to maximize the sensitivity of the search. No limits were placed on level of evidence or timing of the study. Findings were reported according to the PRISMA guidelines Results: After application of inclusion and exclusion criteria, 41 studies were included in this review. Bayesian networks had the highest average AUC (.80), and neural networks had the best accuracy (83.0%), sensitivity (81.5%), and specificity (71.8%). Preoperative planning/cost prediction models (.89, 82.2%) and discharge/length of stay models (.80, 78.0%) each reported significantly higher average AUC and accuracy compared to readmissions/reoperation prediction models (.67, 70.2%) ( P < .001, P = .005, respectively). Model performance also significantly varied across postoperative management applications for average AUC and accuracy values ( P < .001, P < .027, respectively). Conclusions: Generally, authors of the reviewed studies concluded that AI/ML offers a potentially beneficial tool for providers to optimize patient care and improve cost-efficiency. More specifically, AI/ML models performed best, on average, when optimizing preoperative patient selection and planning and predicting costs, hospital discharge, and length of stay. However, models were not as accurate in predicting postoperative complications, adverse events, and readmissions and reoperations. An understanding of AI/ML-based applications is becoming increasingly important, particularly in spine surgery, as the volume of reported literature, technology accessibility, and clinical applications continue to rapidly expand.